Accounting, transparency and governance: the heritage assets problem. Issue 2 (2014) - ,; ,
Abstract : Purpose – This paper aims at offering a contribution which addresses one particular issue – heritage assets – as an exemplar of the challenges facing accounting practices in achieving transparency in government and public services.Design/methodology/approach – After having identified three levels of transparency, a documentary analysis is used as the primary research method.Findings – The investigation carried out reveals that the first level, or minimal level, of transparency is unlikely to be achieved for public organizations with heritage assets, mainly due to deep seated, pernicious problems of asset recognition and valuation.Originality/value – This paper contributes to the debate on what constitutes "good public governance" by examining whether accounting can foster or enhance "good governance" through the lens of transparency.